Effectiveness of Trihalomethane (THM) Precursors Removal in Groundwater Using Coagulant-Disinfectant - Mokhtar Kamal, Nurul Hana (International Journal of Integrated Engineering, 2019)
Trihalomethanes (THMs) is a disinfection byproduct (DBP) which forms when disinfectants react with natural organic matter (NOM) in treated drinking water. The coagulation process using ferric salts was able to remove NOM, a DBP precursor, effectively. This study method included the combination of coagulants (ferric-based) with disinfectant(s), to speed up the treatment process in emergency applications. Groundwater samples were treated using either ferric sulphate or ferric chloride, and chlorine in a series of jar tests. Ferric sulphate application showed a good turbidity removal (50.51%) while UV254 removal using ferric chloride was as high as 80.76%. Most conditions at pH 5.5 formed lower THMs compared to other pH levels, although the THM level at this pH still exceeded the limit set by authorities.